RANCANG BANGUN WEBSITE SISTEM INFORMASI GEOGRAFIS UNTUK PEMETAAN TINGKAT PENCEMARAN UDARA DI INDONESIA - kartika damayanti sugiarto (Universitas Merdeka Malang, 2017)
The Air quality in Indonesia is become worst in day by day these years. The negative impact of air pollution for humans are increasing. In order to feature air conditions in Indonesia we need an application of information systems for mapping the level of air pollution that occurred in Indonesia. This is expected to be able to solve this problem. The objective of this application is providing information that related with air pollution in Indonesia. The method of application development begins with analysis, data completion, program implementation and the latter can be used properly. Predicted results of this application is expected to provide information for the public to be able to see which air pollution and the level of that air pollution which is occurred.DOI: https://doi.org/10.26905/jtmi.v3i2.1282